The impact of migrants' knowledge about their social rights on their subjective wellbeing - Seibel, Verena (Frontiers in Political Science, 2023)
Introduction In this contribution I examine the role of migrants' knowledge about their social rights (system knowledge) for their subjective well-being. Based on the Social Production Function Theory, I expect system knowledge to be positively associated with migrants' well-being. Migrants who are well informed about their social rights are likely to have better access to resources that are crucial for their well-being such as healthcare or financial security. Moreover, I expect that knowledge in certain domains which affect daily life, such as healthcare, matter more than knowledge in other domains, which are life-course specific, such as childcare. Methods I make use of the Migrants' Welfare State Attitudes (MIFARE) data which includes the perspective on the welfare state of migrants from nine different origin countries across three receiving countries: Denmark, the Netherlands, and Germany. Linear regression analyses were applied. Results Results indicate that migrants differ extensively in their social rights knowledge. Moreover, migrants' knowledge about their social rights is indeed positively associated with subjective well-being, though the effect is not equally strong in all three receiving countries and differs by welfare domain (healthcare, childcare, unemployment benefits, social assistance, and state pensions). Discussion Knowledge about social rights matters for migrants' well-being. Policy advisors should therefore pay special attention to migrants' access to information about social right policies in order to increase their well-being.